The domestication of SARS-CoV-2 into a seasonal infection by viral variants - McClelland, Ryley D.; Lin, Yi-Chan James; Culp, Tyce N.; Noyce, Ryan; Evans, David; Hobman, Tom C.; Meier-Stephenson, Vanessa; Marchant, David J. (Frontiers in Microbiology, 2023)
The COVID19 pandemic was caused by the betacoronavirus SARS-CoV-2. SARS-CoV-2 variants have emerged due to adaptation in humans, shifting SARS-CoV2 towards an endemic seasonal virus. We have termed this process 'virus domestication'. We analyzed aggregate COVID-19 data from a publicly funded health care system in Canada and graphed surrogate calculations of COVID-19 disease severity and SARS-CoV2 variant plaque sizes in tissue culture. We observed a decrease in COVID-19 disease severity surrogates after the arrival of the Delta variant, coinciding with significantly smaller plaque sizes. We suggest that SARS-CoV-2 has become more infectious and less virulent through viral domestication.